Dielectric and ferroelectric properties of K2Pb4Nb10O30-Na2Pb4Nb10O30-K6W4Nb6O30 across morphotropic phase region - Mehdiyeva, Rafiga Z.; Mammadov, Ali I.; Jabarov, Sakin H.; Demirci, Niyazi; Coskun, Tuba; Seyidov, MirHasan Yu. (Elsevier Science Sa, 2015)
Ferroelectric ceramics of K2Pb4Nb10O30-Na2Pb4Nb10O30-K6W4Nb6O30 (abbreviated to KPN-NPN-KWN) were synthesized by using a high-temperature solid-state reaction technique. Phase structure, dielectric and ferroelectric properties of the ceramics with composition passing across the morphotropic phase (MP) region in the phase diagram were mainly investigated. Temperature dependence of dielectric constant (epsilon(T)) of KPN-NPN-KWN solid solutions with 30, 50 and 60-mol% NPN were investigated in detail. All samples were characterized by a broad dielectric maximum peak of epsilon(T) at the Curie temperature and weak frequency dielectric dispersion. All compositions exhibited classical diffuse phase transition of a relaxor ferroelectric with a broad peak of dielectric constant induced by the compositional disorder. The K1.36Na1.2Pb3.44W0.56Nb9.44O30 ceramic located on the line 60-mol% NPN in the region of rhombic phase in the vicinity of the MP-region exhibited a high dielectric constant (epsilon similar to 9700) at 1 kHz near the Curie temperature. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Ferroelectricity; Insulators; Chemical synthesis; X-ray diffraction; Grain boundaries; Dielectric response